Unveiling Hango’s Architectural Legacy: Sustainable Building Traditions Through a Community-Centric Approach - Maneya Wadhwa (International Journal of Urban Design and Development, 2024)
Hango, an enchanting village nestled in the picturesque Hangrang valley near the Indian-Chinese border, occupies a remarkable position at an elevation of 15,000 feet in the Kinnaur District of Himachal Pradesh, India. This research paper introduces the distinctive architectural practices of Hango village, focusing on the materials sourcing and processing methods, construction techniques, and the challenges encountered in preserving these practices amidst the growing influence of modernization. Through extensive field visits, interviews with the local community, and careful thematic analysis, this study uncovers the community-centric approach to architecture in Hango, emphasizing the sustainable practices of wood, stone, and mud sourcing, as well as the communal building traditions that shape the village's unique architectural heritage. Hango's strategic location, deliberately positioned away from the path of glacier melt, and its close proximity to the Huyu khud rivelet have significantly shaped the village's setting and agricultural fields. The villagers' deep connection with their environment is reflected in their architectural choices and construction methods. This research not only explores the technical aspects of Hango's architecture but also delves into its community values. The study reveals how architecture manifests the community's identity, history, and social cohesion. It underscores the need to safeguard these traditional practices through a comparative analysis between the traditional and modern practices since they contribute to the village's sustainable development and provide a sense of continuity, belonging, and pride for the resident
Keywords: Building materials sourcing and processing; Community-centric approach; Sustainable construction techniques; Traditional architecture practices